The Meaning of Shopping Experience in TikTok Live Shopping: A Qualitative Study on Millennial Consumers - Nulthazam Sarah; Nur Fadilah Ayu Sandira; Indri Iswardhani; Sri Astuti Nasir; Rostina Rostina (Business Management, 2025)
This study explores the meaning of millennial consumers' shopping experience on TikTok live shopping through a phenomenological qualitative approach. The study involved millennial consumers who actively participate in TikTok live shopping to understand the construction of their personal meaning towards the digital shopping experience. The findings reveal that millennial consumers interpret live shopping as a form of experiential consumption that integrates the dimensions of entertainment, social interaction, and commercial transactions. The process of meaning-formation is influenced by real-time interactivity factors, community dynamics, and hedonistic-utilitarian value balance. Consumers develop trust through parasocial relationships with hosts and collective validation of the community. The study identified the transformation of consumer behavior from deliberate decision-making to intuitive purchasing influenced by social and emotional stimuli. Theoretical implications include contributions to the consumer behavior and social commerce literature, while practical implications provide insights for the development of live commerce strategies that are responsive to millennial consumer expectations in the digital marketplace ecosystem.